Pembelajaran Tajwid Bagi Anak Berbasis Teknologi Informasi - Pulungan, Sahmiar; Dharmawati, Dharmawati (Universitas Muhammadiyah Yogyakarta, 2021)
This community service activity aims to extend the knowledge and to motivate children in reading Al-Qur’an well and correctly using tajwid application. The activity was done in Masjid Babussalam Pasar X Tembung, Percut Sei Tuan District, Deli Regency, Serdang. The activity targets were the children around the environment of Masjid Babussalam. The methods used in this activity were lecturing and practice. There are 3 stages of this implementation activity namely preparation, implementation, and evaluation. The activity results are the increased ability of the children in comprehending and in understanding as well as in using tajwid application in Al-Qur’an learning. If seen from the evaluation, it is found that the children feel enthusiastic and happy in learning Al-Qur’an using this application.